2007
DOI: 10.1007/s10548-007-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Physiological Adaptations Associated with Cross-Education of Strength

Abstract: Cross-education of strength is the increase in strength of the untrained contralateral limb after unilateral training of the opposite homologous limb. We investigated central and peripheral neural adaptations associated with cross-education of strength. Twenty-three right-handed females were randomized into a unilateral training group or an imagery group. A sub-sample of eight subjects (four training, four imagery) was assessed with functional magnetic resonance imaging (fMRI) for patterns of cortical activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
112
2
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 51 publications
9
112
2
10
Order By: Relevance
“…Given that much of the cross-education literature has only considered cross-education effects following unilateral strength training of the dominant right limb (Farthing et al 2007;Hortobagyi et al 2011;Kidgell et al 2011;Lee et al 2009), the objective of this study was to examine the directionality effects of crosseducation following unilateral strength training of either the dominant or non-dominant wrist in right-handed individuals. A secondary objective was to examine the corticospinal responses associated with unilateral strength training and cross-education.…”
Section: Introductionmentioning
confidence: 99%
“…Given that much of the cross-education literature has only considered cross-education effects following unilateral strength training of the dominant right limb (Farthing et al 2007;Hortobagyi et al 2011;Kidgell et al 2011;Lee et al 2009), the objective of this study was to examine the directionality effects of crosseducation following unilateral strength training of either the dominant or non-dominant wrist in right-handed individuals. A secondary objective was to examine the corticospinal responses associated with unilateral strength training and cross-education.…”
Section: Introductionmentioning
confidence: 99%
“…Our results have shown that MIT training also added benefits to improve paretic muscle strength in hip flexors and extensors, knee extensors and dorsiflexors. Neural adaptation is a key factor for strength gain in voluntary skeletal muscle training [36]. Earlier studies on MIT and muscle strength had shown that mental practice with motor imagery actively changes in central programming process such as motor planning which enhances for neural adaptation for maximal voluntary contraction (MVC) [37] and also kinesthetic imagery training could alter the greater activation in motor units which may attribute for our present findings [38][39][40].…”
Section: Discussionmentioning
confidence: 54%
“…Many related studies have been undertaken recently, as cross-training can strengthen the muscular power of body parts that are hard to train directly 12) . These studies have shown that muscular and endurance training for limbs of one side can enhance the muscular power, function, and endurance of the limbs on the other side due to the interlateral transfer of training 13) and can enhance their performance function 14) . Muun et al (2004) conducted a meta-analysis to examine the effect of training on one side on muscular strength of the other side and reported that cross-training can be effective.…”
Section: Discussionmentioning
confidence: 99%